Original article Interleukin 17 receptor in multiple sclerosis patients treated with interferon β-1a - Michałowska-Wender, Grażyna; Biernacka-Łukanty, Justyna; Lasik, Zofia; Jernas, Łukasz; Wender, Mieczysław (Folia Neuropathologica, 2011)
Interleukin 17 (IL-17) and its receptor IL-17R1 produced by T-helper cells named Th17 are involved in the pathology of autoimmune diseases. In contrast to the at least partially explained role of IL-17 in pathology of multiple sclerosis, the significance of IL-17R in MS is unclear. Therefore we have studied the expression of IL-17R in the stable phase of multiple sclerosis treated by interferon β-1a. The studied material consisted of 20 MS patients with relapsing-remitting form of the disease, and fulfilling the diagnostic McDonald et al. criteria. The patients were treated subcutaneously every second day with 30 mg of interferon β -1a (Betaferon). The interleukin 17 receptor level was measured by the ELISA immunoassay test using RayBio human IL-17R ELISA kit. After three months of therapy with interferon β -1a the level of IL-17R was significantly higher than that established at the starting point. The level of IL-17R after 6 months of therapy was insignificantly higher than established in the previous study group (3 months of therapy). While it remains difficult to pinpoint the exact significance of upregulation of IL-17R in the early period of therapy, the present findings should be taken into account when considering the pharmacodynamics of interferon action in MS in view of the opinions on the crucial role of IL-17 in pathology of MS and suggestions that it may constitute a drug target in autoimmunological diseases.